Safety and Efficacy of Methanol Fraction of Moringa oleifera as Antihypertensive in L-NAME Induced Hypertensive Rabbits: Bedside to Bench, Implications for Bench Back to Bedside - Adedapo, A.D.A.; Jegede, O.T.; Omobowale, T.O.; Nabofa, W.; Oyagbemi, A.A.; Adedapo, A.A. (Journal of Nutritional Therapeutics, 2018)
Context: Hypertension, a global menace requires innovative research into the use of Moringa oleifera being promoted and traditionally used as alternative therapy. Objective: To innovatively evaluate the mechanistic effect, safety and efficacy of the methanol fraction of M. oleifera (MMO) leaves on L-NAME induced hypertensive rabbits. Methods: Rabbits were divided into six groups: Control, L-NAME alone, L-NAME with 100, 200 or 400 mg/kg of MMO and enalapril. Inclusion and exclusion criteria were similar baseline parameters and Day 3 systolic blood pressure (SBP) less than baseline SBP respectively. The primary outcome was a 10% reduction of SBP on Day 21. Enalapril group was excluded from analysis. Safety was assessed with liver and renal functions, hydrogen peroxide and nitric oxide concentrations to elucidate mechanistic effect. Results: Moringa 100 mg/kg, 200 mg/kg and 400 mg/kg reduced SBP by 4.75, 18.00 and 15.25 mmHg (F=22.123, p=0.000). SBP control was achieved with MMO 200mg/kg, 14% reduction and 400mg/kg, 12% reduction. Nitric oxide concentration, 0.06, 0.094 and 0.114mmol (F= 30.255, p= 0.000) dose-dependently increased and was most predictive of SBP control (r2=0.802, p=0.000). Nitric oxide production was inversely related to heart/body weight ratio which was dose-dependently reduced. MMO reduced hydrogen peroxide and ALT level but no significant effect on urea, HDL, and TG. Conclusion: MMO reduced SBP and dose-dependently increased nitric oxide concentration in L-NAME induced hypertensive rabbits. The effect may be mediated via activation of nitric oxide pathway. MMO demonstrated a potent anti-oxidant activity and safety. Effect on ventricular hypertrophy needs further evaluation.